THE INFLUENCE OF BRAND IMAGE AND PRICE PERCEPTION ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION (Study of Samsung Smartphone Users among Students in Surabaya) - Agung Prabowo; Kristiningsih; Bambang Setyadarma (P3I UMSurabaya, 2024)
Mature This all line in the world already is at in the era of digitalization . Digital technology does not only used For industry needs but also become primary human needs as tool For communicate even For Work . So that need will tool telecommunication specifically product smartphones are one of them high demand _ on the market . Marketing management research This want to test and see How level loyalty Samsung users as the best- selling smartphone product on the market specifically among students in Surabaya . Research purposes This is For know Satisfaction customer as variable mediation between image brand and perception price to loyalty customer . Research methods used _ is method quantitative , with a sample of students in Surabaya who use Samsung smartphones . Research result This that satisfaction customer influential significant in mediate between image brand and perception price to loyalty customer.